Real-world evidence of glycemic control among patients with type 2 diabetes mellitus in India: the TIGHT study - Surendra S Borgharkar; Soma S Das (BMJ Open Diabetes Research & Care)
Objective To determine glycemic control in adult patients with type 2 diabetes receiving antidiabetic therapy as part of routine healthcare in India.Research design and methods This was a retrospective analysis of cross-sectional data of patients with type 2 diabetes receiving oral hypoglycemic agents (OHAs) with or without insulin between 2015 and 2017. We assessed proportion of patients with uncontrolled glycemia and performed logistic regression to evaluate its association with various risk factors and microvascular complications.Results A total of 55 639 eligible records were identified; mean age of patients was 54.31 (±11.11) years. One-third of the study population had microvascular complications, predominantly neuropathy. Nearly 76.6% of patients had uncontrolled glycated hemoglobin (HbA1c) ≥7% (53 mmol/mol); 62% of these patients had HbA1c between 7% and 8% (53–64 mmol/mol). Glycemic control from combination of OHAs with or without insulin varied between 14.2% and 24.8%. In multivariate analysis, factors statistically associated with uncontrolled glycemia were obesity (OR: 1.15), hypertension (stage I OR: 1.65 and stage II OR: 2.73) and diabetes duration >5 years (OR: 1.19) (p<0.001). Similarly, the odds of having any microvascular complication increased with duration of diabetes (past 1–2 years, OR: 1.67; 2–5 years, OR: 2.53; >5 years, OR: 4.01; p<0.0001), hypertension (stage I, OR: 1.18 and stage II, OR: 1.34; p<0.05) and uncontrolled HbA1c (OR: 1.28; p<0.0001).Conclusions Indian population with type 2 diabetes has a high burden (76.6%) of poor glycemic control. This study highlights the need for early implementation of optimum diabetes pharmacotherapy to maintain recommended glycemic control, thereby reducing burden of microvascular complications.